Construction contract administration in Malaysia using DFD: a conceptual model - Chong, Heap Yih; Balamuralithara, B.; Chong, S. (Emerald Group Publishing, 2011)
AbstractPurpose – The purpose of this paper is to propose a conceptual model which is aimed at assistingend-users, i.e. construction practitioners who are without a proper legal background for effectiveadministration of construction contracts, to enable them to make correct interpretations and decisionsin dealing with vast amount of legal information.Design/methodology/approach – This study proposes the application of data warehousetechnology in the contract administration process of the construction industry. Upon identificationof a comprehensive list of problems associated with construction contracts based on the feedback from12 reputed experts in the construction industry, a conceptual model is developed using a data flowdiagram.Findings – The results show that data warehouse technology is feasible and practical to theconstruction practitioners in the contract administration process.Research limitations/implications – This research focuses only on the development of aconceptual model and thus the practicability aspect of the model is a major concern. As such, theresulting practical implications are limited and are constrained only to the construction industry inMalaysia, raising the question of generalizability of the proposed model, as well as across differentindustries and countries.Practical implications – It is posited that the proposed conceptual model, when implemented,would enable construction practitioners to administer construction contracts with better clarityand accuracy, so that interpretation errors and disputes can be mitigated. This will facilitate thedevelopment of harmonious working relationships.Originality/value – The application of data warehouse technology in contract administration israther new in the construction industry. The conceptual model thus offers a more effective and proactiveapproach in construction contract administration towards dispute resolution and/or prevention.